FIGHTS AT SCHOOL: A VISION OF ACADEMICS IN PHYSICAL EDUCATION (Fiep Bulletin - online, 2013)
The fights in the school can act as an educational tool for learning and interaction for students, as this can bring many benefits to the user, detaching motor development, cognitive and social-emotional. The aim of this study was to identify the views of academics in Physical Education UNIABEU, in terms of pedagogical practice of fights in Physical Education. The methodology was carried with a out field research through interviews with the students of Degree and Bachelor Course in Physical Education of UNIABEU through closed questionnaire and also through a literature review of authors in the area of Physical Education that relate to insert content Fights in Physical Education classes. Verified through the results that respondents had little contact with the contents struggles in Physical Education. The activities more approached were those with more sporting character. The academics said they intended to use the struggles content in their future pedagogical practices because they believe that the struggles helps expand knowledge about the culture of body movement and still break paradigms on the practice of struggles. The fieldwork allowed the conclusion that the School Fights are still have a big blockade, however the literature review demonstrates how the struggles contribute content for physical education at school. It is recommended that further studies be made ??in the search for a comparison of the view of academics from different educational institutions supeior (IES) Physical Education on the issue of inclusion of the content of struggles in Physical Education.
Keywords: Fights; School Physical Education; Academic Physical Education